2020
DOI: 10.1371/journal.pone.0238716
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of transgenic (Bt) and non-transgenic (non-Bt) cotton mulches on weed dynamics, soil properties and productivity of different winter crops

Abstract: The introduction of transgenic cotton (Bt-cotton) for controlling bollworms has resulted in increased production; however, the residual effects of mulches from Bt-cotton are poorly understood. Therefore, the current study evaluated the impact of Bt and non-Bt cotton mulches on soil properties, weed dynamics and yield of winter crops sown after cotton. Three different winter crops, i.e., wheat (Triticum aestivum L.), canola (Brassica napus L.) and Egyptian clover (Trifolium alexandrinum L.) and two mulch types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…chinensis . Several studies on weed species have also suggested that extracts of various plants effectively suppress weed populations [ 55 60 ]. Therefore, these are valuable resources for pest management.…”
Section: Discussionmentioning
confidence: 99%
“…chinensis . Several studies on weed species have also suggested that extracts of various plants effectively suppress weed populations [ 55 60 ]. Therefore, these are valuable resources for pest management.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several plant residues decreased weed competition because of their allelopathic potentiality (Anzalone et al 2010). The negative impacts of weeds could be dwindled by employing the allelopathic potential of crops using mulches (Riaz Marral et al 2020). Significant increase in relative water content and photosynthesis efficiency and decrease in weed competition were obtained with using of soil mulching (Abd El-Mageed et al 2016;El-Metwally et al 2022).…”
Section: Treatmentmentioning
confidence: 99%
“…Weeds exert negative impacts on quality and quantity of agricultural products; thus, reduce farmers’ profits to a significant extent [ 10 ]. Weeds compete with crop plants either through competing for moisture, sunlight, nutrients, and space or through secreting allelochemicals, which adversely impact seed germination and growth of crop plants [ 11 , 12 , 13 ]. Nevertheless, weeds produce significant number of seeds, which are deposited to soil seed bank; thus, laying the foundation for future weed infestation [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, plant-based natural products that could serve as alternatives to herbicides have been focused on weed management research globally [ 28 ]. Residues’ incorporation of allelopathic crops, and inclusion of such crops in rotation could improve weed control [ 8 , 11 , 29 ]. The crops with high allelopathic potential include sunflower, rye, wheat, rice, barley, and sorghum, which have been shown to suppress weed flora in different crops [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%